Algorithm for assessing the total 10 years risk of death from cardiovascular diseases in women 25-64 years old in Tyumen (Tyumen risk scale) - G. S. Pushkarev; S. T. Matskeplishvili; V. A. Kuznetsov; E. V. Akimova (Евразийский Кардиологический Журнал, 2021)
Purpose: To define total 10-year cardiovascular mortality risk in Russian females in dependence on traditional and psychosocial risk factors (RF) and to design the algorithm of its estimation.Methods. The study included non-organized population of Central Administrative district of Tyumen city. Epidemiological study, based on the representative selection of 1000 females aged 25-64 years. Screening respond was 81.3%. Cardiovascular mortality rate within 10 years was studied. Totally, 31 cases of cardiovascular death were registered in female cohort within 10year follow-up. We used a multivariate Cox regression model to estimate hazard ratio (HR) and confidence interval (CI). Relations between mortality rate and factors such as age, smoking, education, occupation, marital status, systolic and diastolic blood pressure (SBP and DBP), body mass index, total cholesterol, cholesterol of low and high density lipoproteins were analyzed.Results. To build a model of total cardiovascular risk, six statistically significant indicators were selected: age (HR – 1.099, 95% CI 1.032-1.1.69), SBP (1.026, 95% CI 1.011-1.041), primary education (4.315, 95% CI 1.878-9.910), work associated with heavy physical labor (4.073, 95% CI 1.324-12.528), executives (3.822, 95% CI 1.386-10.537) and marital status (2.978, 95% CI 1.197-7.409). Based on these data, model for total cardiovascular mortality risk in females was designed with good predictive accuracy (AUC was 0.882, 95% CI – 0.833 – 0.930).Conclusion. Thus, created mathematical model, built based on statistically significant traditional and psychosocial RF, makes it possible to effectively predict the total cardiovascular risk at the individual level in the female population.